PENGARUH KILN FEEDING TERHADAP KINERJA ALAT ROTARY KILN PABRIK II PT. SEMEN BATURAJA Tbk DITINJAU DARI SPESIFIC FUEL CONSUMPTION - Marambang, Alfi Yory; Safaruddin, Safaruddin; Muzzaki, Mukti Mabrur (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
As is known, cement is one of the most important materials needed in infrastructure development. The main equipment for the cement production process is the rotary kiln which is used as a process of burning, mixing and decomposition of the kiln feed which is a mixture of around limestone (70% - 90%), clay (about 10% -30%) , and the rest (0 – 10%) is correction material in the form of iron sand, and silica sand becomes clinker. Specific Fuel Consumption (SFC) is an indicator to determine the performance of the rotary kiln tool, and as an industrial benchmark to save production costs. This calculation is made based on actual data taken from the Central Control Room (CCR) and Quality Control (QC) Laboratory of From the calculation of the mass balance, energy balance, and SFC value, the results for the lowest SFC value were obtained on July 26, 2023, which was 628.77 kcal/kg while the highest SFC value was obtained on July 29, 2023, which was 724.01 kcal/kg. Concluded the SFC is inversely proportional to the number of kiln feeding. The greater the number of kiln feeding, the smaller the SFC value.